2018
DOI: 10.1111/bju.14210
|View full text |Cite
|
Sign up to set email alerts
|

The fragility of statistically significant findings from randomised controlled trials in the urological literature

Abstract: The results of urology RCTs that study dichotomous outcomes and report statistically significant differences between groups are sometimes fragile and depend on few events. Urologists should interpret these RCTs cautiously, particularly when the number of participants lost to follow-up exceeds the Fragility Index. Routine reporting of Fragility Index values alongside P values may provide additional guidance about the robustness of statistically significant findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 60 publications
3
14
1
Order By: Relevance
“…Therefore, an additional metric like the FI should be reported together with the results. On the other hand, a strong negative correlation between the FI and sample sizes was detected in some studies [27][28][29][30][31] . In our study, we could not detect such a correlation because most trials included in our review had small sample sizes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, an additional metric like the FI should be reported together with the results. On the other hand, a strong negative correlation between the FI and sample sizes was detected in some studies [27][28][29][30][31] . In our study, we could not detect such a correlation because most trials included in our review had small sample sizes.…”
Section: Discussionmentioning
confidence: 96%
“…An approach named Fragility Index was introduced by FI was calculated for different medical literatures as urologic, orthopedic surgery, giant cell arthritis, anesthesiology and etc. [29][30][31][32] . There was no research found, which evaluated the robustness of the results for randomized controlled trials using diagnostic imaging techniques and the Fisher exact test together before.…”
Section: Discussionmentioning
confidence: 99%
“…Narayan et al reported an FI of 3 (IQR 1-4.5), where 67.5% of the trials had a number of patients lost to follow-up greater than the FI in an analysis of RCTs in the field of urology [11]. Likewise, a study examining RCTs in spine surgery reported an FI of 2, where 25% of the trials had a number of patients lost to follow up greater than the FI [14].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the fields of urology and spine surgery have, however, reported a positive correlation between FI and sample size, while other studies have demonstrated a weak positive correlation. A study in pediatrics published in 2017 reported no correlation between FI and sample size [11][12][13][14][15]. The relationships between FI and sample size, along with other parameters, are inconsistent among several studies and a concrete understanding is yet to be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation